Burger Wuss - Anderson, M.T (Walker Books Ltd, 2000)
Anthony has never been able to stand up for himself $1 (B- that is, not until his girlfriend is in someone else$1 (Bs arms. Then Anthony vows revenge and devises the Plan. It begins with getting a job at the fast-food restaurant where his nemesis happens to be a star employee. But when the Plan is finally in place, will Anthony$1 (Bs hunger for revenge be satisfied? Will he prove he$1 (Bs not a wuss?s
Keywords: Adolescence; Juvenile Fiction